An updated meta-analysis of hemodynamics markers of prognosis in patients with pulmonary hypertension due to left heart disease. (3rd October 2022) - Caravita, S; Baratto, C; Soranna, D; Dewachter, C; Bondue, A; Zambon, A; Badano, L P; Parati, G
Abstract: Background: Pulmonary hypertension (PH) is associated with a poor prognosis in patients with left heart disease (LHD). Several hemodynamic variables have been shown to predict outcome, including pulmonary vascular resistance (PVR), pulmonary artery compliance (PAC), and the diastolic pressure gradient (DPG). We sought to provide an updated analysis on the association of these variables with prognosis in PH-LHD. Methods: We performed a systematic literature review including studies reporting association measurements between DPG and/or PVR and/or PAC and death in PH-LHD patients. These hemodynamic variables were extracted to estimate the pooled hazard ratio (HR) of adverse outcome for each one, and cumulative meta-analysis was performed to investigate temporal trends in the effects reported in the literature as well as the impact of sample size. Results: 17 articles were identified, including 9716 patients with LHD, heterogeneous in terms of age, sex, and etiology of cardiac disease. In this large population, we found that PVR (HR, 1.09; 95% CI: 1.06–1.12), DPG (HR, 1.02; 95% CI: 1.01–1.02) and PAC (HR, 0.73; 95% CI: 0.76–0.81) were associated with an increased risk of adverse outcome, albeit with a less solid performance of DPG (Figure 1). Similar results were found when hemodynamic variables were analyzed according to the thresholds commonly applied in clinical practice, or subdividing cohorts according to the underlying LHD (either heart failure with preserved or reduced left ventricular ejection fraction, or valvular heart disease). Furthermore, cumulative metanalysis indicated that these results are consistently stable since 2018 (Figure 2). Conclusions: Despite the heterogeneity of PH-LHD group and the intrinsic limitations of each variable, PVR, DPG, and PAC have an established prognostic value in PH-LHD. The strongest correlation with PVR and PAC supports their use in defining disease severity and identifying a subgroup of patients at higher risk of adverse outcome. We believe that these results are consistent through the years and unlikely to change with the addition of further studies. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship.